Retained copper fragments following removal of a copper intrauterine device: Two case reports - Marina Dubovis; Naglaa Rizk (Elsevier, 2020)
Intrauterine devices (IUDs) are safe, cost-effective, and reliable contraceptives, and are gaining popularity worldwide. While complications associated with IUD use are rare, they range from expulsion to uterine perforation. Numerous reports have been published regarding the sequelae of intraperitoneal copper IUDs or retained fragments following the removal of a fractured device. No data exist, however, on the intraperitoneal retention of copper following the removal of an otherwise intact IUD. Here we present two patients in whom copper IUDs were found to have missing fragments of copper wire despite removal of an otherwise intact IUD found in utero. We caution providers to examine all removed devices carefully, to surgically address intraperitoneal copper in order to mitigate adhesion formation, and to counsel patients about this potentially serious complication.